Ideals and Virtual Realities - Enrique Canessa (Kassel University Press, 2021)
Abstract—A main step for world’s progress is to keep sharing ever-present Ideals for science and education within today’s Virtual Realities. On-line education is transforming human society to new levels in the way people teach and learn during the ongoing SARS-CoV-2 pandemic. There is an increasing interest in having more and more reliable, fast and simple apps to communicate and also to record, assemble and distribute videos and lectures in the fields of Physics & Maths still using traditional didactic methods. We describe here how to accurately reproduce chalkboard classes for the popular YouTube video platform using OpenEyA-YT. The audience can thus be expanded over continents to help mitigate the effects of physical isolation.